The Effect of Adding Different Amounts of Turmeric (Curcuma domestica) on The Consumer Acceptance Level of Milkfish (Chanos chanos) Amplang - aulia, nabila; Andriyono, Sapto; saputra, eka (Journal of Marine and Coastal Science, 2023)
Turmeric as a natural dye contains curcuminoids which are beneficial for the body and have the potential to be applied in food stuffs such as in amplang. Milkfish amplang (Chanos chanos) is a snack made from typical Indonesian fish which is quite popular in society. This study used experimental laboratory research methods which aimed to determine the effect of adding the amount of turmeric (Curcuma domestica) on the level of consumer acceptance of the chemical and organoleptic characteristics of milkfish amplang. The design used was a completely randomized design (CRD) with one factor, namely the addition of turmeric to the production of milkfish amplang consisting of four treatments and three repetitions. The results showed that there was a significant difference between the treatments (p<0.05), the highest nutritional value was found in milkfish amplang with the addition of 0.5 g of turmeric with an average value of water content (2.64%), ash content (1.75%), protein content (10.54%), fat content (7.51%), and carbohydrate content (77.53%). Organoleptic test results showed that the best treatment was the addition of 0.5 g turmeric with average values for color (8.60), smell (8.40), taste (8.53), and texture (8.80).